2016
DOI: 10.1186/s13002-016-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

Food taboos and myths in South Eastern Nigeria: The belief and practice of mothers in the region

Abstract: BackgroundPoor nutritional practices especially in pregnancy and early childhood can result in dire consequences in the growth and development of a child.MethodsThis study using purposive sampling enrolled 149 women who had carried at least one pregnancy to term in Enugu south east Nigeria. Logistic regression analysis was used to assess association between avoidance of certain food in pregnancy and selected socio-demographic factors.ResultsApproximately 37 % of respondents avoided some foods in pregnancy due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 16 publications
(11 reference statements)
13
70
2
7
Order By: Relevance
“…This result is in line with other findings from Hadya zone and Shashemene district of Ethiopia and South Eastern Nigeria that reported women's claim to difficult delivery as the result of increased size of the fetus due to consumption of nutritious foods [9,10,28,29]. This may be due to lack of knowledge on the need for weight gain during pregnancy for the health of the fetus and the mother.…”
Section: Discussionsupporting
confidence: 80%
“…This result is in line with other findings from Hadya zone and Shashemene district of Ethiopia and South Eastern Nigeria that reported women's claim to difficult delivery as the result of increased size of the fetus due to consumption of nutritious foods [9,10,28,29]. This may be due to lack of knowledge on the need for weight gain during pregnancy for the health of the fetus and the mother.…”
Section: Discussionsupporting
confidence: 80%
“…The current study was in the same vein with (12), who reported that, most of the studied mothers denied eating egg to their children, as well it was in line with (13) who revealed that most of the studied mothers do not give egg to their children. The belief is that it leads children to theft when grow older.…”
Section: Discussionsupporting
confidence: 84%
“…This nding is again supported by the ndings from the study in Ghana and Kenya that showed consumption of Eggs make the fetus large (18,19). This nding is again supported by the study nding from Nigeria where consumption of eggs is prohibited during pregnancy because it is feared that the children may develop bad habits after birth (4). The difference supports literature that indicates there is no single reason but several reasons for the belief and adherence to food taboos (20).…”
Section: Discussionsupporting
confidence: 67%